Energy Efficient Homes: Design Strategies and Economic Analysis - Shrestha, Anjana (Journal of Engineering Issues and Solutions, 2025)
The residential sector in Nepal is the largest consumer of energy. Despite the growing interest in energy-efficient (EE) building practices, there is a misconception among the stakeholders that EE homes are more expensive than Business-as-Usual (BAU) homes due to a lack of awareness about life cycle cost benefits. Using case study methodology, the study is structured to analyze the economic aspect of two EE homes and one BAU home in Kathmandu’s temperature climate, based on initial incremental cost, Net Present Value (NPV), and pay-back period over a 40-year lifespan. The results show that EE homes have a higher initial incremental cost of up to 22.19% compared to BAU home. However, there is an annual energy cost savings, which demonstrates a lower NPV of EE homes up to 20.30%, indicating long-term economic benefits. The life-cycle analysis shows that the initial incremental cost can be returned within a pay-back period of 4.3 years for the EE home with brick cavity wall and 10 years for the EE home with rammed earth wall. The findings show that the EE design strategies, though requiring initial incremental cost, have substantial operational savings and low NPV of cost, making them cost-effective on a long-term basis. This study suggests the integration of EE strategies in the residential practices of Nepal at the policy level, guided by cost-benefit analysis.